Effects of different stirrer modes on the physicochemical properties of vegetables during cooking. (23rd January 2023) - Ning, Meng; Zhang, Fan; Deng, Qian; Chen, Yang; Chen, Jie; Wang, Zhaojun
Summary: The coronavirus disease‐19 (COVID‐19) pandemic caused dietary changes. Humans reduced social activities to prevent the spread of COVID‐19, which led to increasing demand for machines to help cook. This work studies the effect of different stirrer modes on the texture of celery, asparagus, green peppers, and spinach during the cooking process and the functional loss of components in vegetables by measuring the changes in vitamin C, total polyphenols, and total flavonoids. The results showed that colour changes and loss of nutrients in each vegetable varied under different stirrer modes. Stirring was found to be the best mode for cooking all four vegetables. In addition, there was a positive correlation between the a* value and functional components during the cooking process, which means that the colour difference and nutritional loss of vegetables can be modulated together. This study provides theoretical guidance for developing the stirring unit in a cooking machine. Abstract : Materials; Cooking mode; Properties analysis; Celery; Spinach; Asparagus; Green pepper; Manual stir fry; Roller; Jolt; Stir; Chromatic aberration; Microstructure; Total phenolics; Total flavonoids; Vitamin C; Sensory evaluation.